Relationship between Characteristics of Inpatients with Typhoid Fever (TF) and Length of Stay (LOS) in the Hospital - Nugraheni, Sri Wahyuningsih; Darul, Ilyas Syafiq; Widigdya, Aquamarine Lathifatunniisaa’ Putri; Sari, Sella Yulia (Global Health Science Group, 2024)
Patient characteristics are unique characteristics that each patient has. Length Of Stay (LOS) between patients varies depending on the patient's condition. Purpose: This study aimed to determine the relationship between the characteristics of Typhoid Fever inpatients and LOS. Method: This type of research is analytical research. The research sample was 203 medical record documents. Data collection using interviews, observations, and work tables. Data processing by collecting, editing, tabulating, calculating, and presenting data. Results: Univariate analysis found that the highest LOS was in the less than ideal category (<6 days), the highest age characteristics were in young people and adults (15-49 years), the highest gender was male, the highest payment method was in the government insurance category, the highest exit method was in the homecoming category, the highest occupation was in the unemployed/not yet employed category. The results of the bivariate analysis of the chi-square test showed the characteristics of age (p = 0.012), gender (p = 0.473), payment method (p = 0.485), exit method (p = 0.570), and occupation (p = 0.021). Conclusion: There is a relationship between age and occupation characteristics with LOS, and there is no relationship between gender characteristics, payment method and exit method with LOS.